2015
DOI: 10.1038/ncomms7223
|View full text |Cite
|
Sign up to set email alerts
|

Wide-angle planar microtracking for quasi-static microcell concentrating photovoltaics

Abstract: Concentrating photovoltaics offer a way to lower the cost of solar power. However, the existing paradigm based on precise orientation of large-area concentrator modules towards the Sun limits their deployment to large, open land areas. Here, we explore an alternate approach using high-efficiency microcell photovoltaics embedded between a pair of plastic lenslet arrays to demonstrate quasi-static concentrating photovoltaic panels o1 cm thick that accomplish full-day tracking with 4200x flux concentration ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…However there is no physical requirement that this 'rotational' approach to sun tracking is the only possible strategy. For example, it has been demonstrated that with appropriate optical design, tracking over a wide angular range may be achieved via small lateral translations of a collecting element [6,7], or by incorporating an optically active element which can vary its optical properties in response to the changing solar angle to create a 'self tracking' system that can track the sun reactively with no external inputs [8,9]. It has been proposed that tracking may be achieved via a localized, light-activated change in transparency to create a concentrating light trap with a dynamic aperture that moves in response to the changing solar angle to admit light over a wide angular range ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However there is no physical requirement that this 'rotational' approach to sun tracking is the only possible strategy. For example, it has been demonstrated that with appropriate optical design, tracking over a wide angular range may be achieved via small lateral translations of a collecting element [6,7], or by incorporating an optically active element which can vary its optical properties in response to the changing solar angle to create a 'self tracking' system that can track the sun reactively with no external inputs [8,9]. It has been proposed that tracking may be achieved via a localized, light-activated change in transparency to create a concentrating light trap with a dynamic aperture that moves in response to the changing solar angle to admit light over a wide angular range ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The higher assembly cost arises from the need to put PV cells at each of the focus points of the array of primary optical elements. 6,[10][11][12][13] In contrast to the stepped waveguide design, [7][8][9] in the fully planar concentrator design (first proposed by Karp et al 5,6 ) sunlight collected by each aperture of the arrayed primary element (mirror or lens) is coupled into a slab waveguide using localized injection features such as prisms or microspheres. The approach using light guides for primary concentration has been commercialized by Morgan Solar.…”
Section: Introductionmentioning
confidence: 99%
“…The projected area [6] of a module decreases according to I = I sun · cos(elevation). Alternatively, micro-trackers form an interesting alternative that does not require to tilt the complete module [46].…”
Section: Incoupling Of Diffuse Light By External Light Trappingmentioning
confidence: 99%